The Influence of Communication Patterns and Stakeholder Roles on Social Solidarity among the Suku Anak Dalam, Pematang Kabau Village, Sarolangun, Jambi - Alhaudhi, Muhammad Alhaudhi Dzuhri; Amanah, Siti; Sarwoprasodjo, Sarwititi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pembangunan Nasional Veteran Jakarta, 2025)
The Suku Anak Dalam (SAD) in Jambi is a remote indigenous community that continues to uphold ancestral traditions, including animistic beliefs, while facing complex social and economic challenges. Various empowerment programs have been implemented, yet their effectiveness remains limited, particularly in terms of communication. Top-down communication patterns used by stakeholders often overlook local needs, aspirations, and Indigenous knowledge, which should serve as the basis for development rooted in local wisdom. This study examines how communication patterns and stakeholder involvement influence the social solidarity of the SAD community. Using a mixed-methods approach, data were collected from 107 respondents through surveys, in-depth interviews, and participatory observation, and analyzed with SMART PLS 4.0. The findings show that communication patterns significantly shape the level of social solidarity among the SAD. Stakeholders do not have a direct influence on social solidarity; however, they contribute indirectly by enhancing community participation, which subsequently affects social cohesion. The key factor reinforcing social solidarity is the communication pattern itself. These results highlight that traditional and modern forms of communication and interaction play a more effective role in strengthening social cohesion within the SAD than direct stakeholder interventions.